Prevalence of T3 thyrotoxicosis and it’s management in new onset thyrotoxicosis patients: a prospective observational study - Singh, Shailendra Kumar; Singh, Rina; Bedi, Sonam; Pandey, Arun Kumar; Tiwari, Alankar; Rai, Pradeep Kumar (International Journal of Advances in Medicine, 2024)
Background: T3 toxicosis is a subtype of thyrotoxicosis where total triiodothyronine (TT3) level is high but total thyroxine (TT4) level is normal in presence of suppressed thyroid stimulating hormone (TSH). Accurate and rapid diagnosis is crucial in management of T3 toxicosis. Methods: In this prospective observational study from India, newly diagnosed thyrotoxicosis patients were enrolled. T3 toxicosis patients were diagnosed based on diagnostic criteria. T3 toxicosis patients were randomized into two arms, based on dose of carbimazole (CBZ) used for treatment. All patients are following up for 12-14 weeks. Results: Prevalence of T3 toxicosis was 8.5% in this study. 75% were diagnosed as Grave’s disease (GD) and 25% were diagnosed as toxic nodular goiter (TNG). Low dose (5 mg/day) of CBZ is safer and more effective than higher dose (20 mg/day). Conclusion: Present study suggests that a significant number of patients with thyrotoxicosis are suffering from T3 toxicosis. So, for correct diagnosis of thyrotoxicosis one should investigate for TT3, TT4 and TSH, otherwise we can misdiagnose the T3 toxicosis as subclinical thyrotoxicosis (SCT). Majority of T3 toxicosis patients are diagnosed as GD. Low dose of CBZ is very much effective and safe in these patients. We recommend low dose of CBZ in all patients with T3 toxicosis.